Penilaian Situs E-Government Dengan Metode Webqual Dan Importance Performance Analysis - Yudha Koessala Puja Andhika (Jurnal Teknik Industri, 2016)
Lapor.go.id is a website to aspirate and complaints were easily accessible and integrated in order to increase community participation in monitoring programs and the performance of the government to implementation of public development and services. This research was descriptive quantitative approach using WEBQUAL dimensions namely usability, information, and service interaction that were assessed based on the perspective of performance and importance. Besides that, this research was conducted to investigate the user satisfaction on the website’s performances. Based on the research result shows that users are satisfied with the website’s performance with the satisfaction index value of 73.02%. Beside that, It is known that the website’s attributes of poorly performing and need to be improved are attributes related to the website’s interfaces, website’s competency, updated informations, detailed informations, and information that is easily understood.